ROLE OF THE NCO IN THE SADF - Heitman, Helmoed-Romer (Scientia Militaria - South African Journal of Military Studies, 2012)
Consider a highly successful olympic athlete who happens to be an equally successful and respected nuclear physicist by profession. Ignore, please, that this notion of a truely amateur sportsman may be rather quaint and old-fashioned. Returning to our veritable superman, we would expect to find him a highly intelligent, strongly motivated, extremely healthy and fit individual.Let us now assume that he is stricken with some terrible disease that causes his bones to soften or disintegrate until they can no longer do their job. Neither his undoubted intellect, nor his equally undoubted brawn, nor his strong motivation, will be able to prevent him being transformed into a helpless, floppy, wheezing mound of tissue that will soon expire rather unpleasantly. Even external aid could not do much to help.